Chronic inflammation is correlated with percentage of body fat independent of the burden of infection - Vahdat, K.; Azizi, F.; Zandi, K.; Assadi, M.; Nabipour, I. (2012)
The aim of this population-based study was to investigate the association of the percentage of body fat (BF) and high-sensitivity C-reactive protein (hs-CRP) when the infectious burden was adjusted for. A total of 1,546 subjects were randomly selected. BF was determined using bioelectrical impedance analysis. Sera were analyzed for IgG antibodies to Chlamydia pneumoniae, herpes simplex virus type 1, Helicobacter pylori, and cytomegalovirus using ELISA. Measurement of C-reactive protein (CRP) by a high-sensitivity CRP assay was performed. A linear relationship between an increase in the number of pathogens and CRP concentrations was observed (p = 0.007). Age-adjusted serum hs-CRP levels were correlated with percentage of BF in men (r = 0.28, p < 0.0001) and women (r = 0.37, p < 0.0001). In multiple regression analyses, hs-CRP showed significant correlations with percentage of BF after controlling for age, sex, cardiovascular risk factors, and the infectious burden was divided into two, three, and four pathogens (beta = 0.24, p < 0.0001), (beta = 0.2 1, p < 0.0001), and (beta = 0.23, p = < 0.0001), respectively. In conclusion, there was a strong association between hs-CRP and percentage of body fat independent of viral and bacterial pathogens that had been previously associated with coronary artery disease as well as carotid atherosclerosis.